THE ROLES OF EDUCATORS (DIDACTIC, REFLECTIVE, AFFECTIVE) TO ENHANCE MOTIVATION TO LEARN SOCIAL SCIENCE - Nur Isroatul Khusna; Dwi Astuti Wahyu Nurhayati; Ramadhani Lausi Mkumbachi; Linda Mayasari (Program Studi Pendidikan Ilmu Pengetahuan Sosial, Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
During the COVID-19 pandemic, student learning activities with respect to learning interest gradually decreased. This is due to the implementation of distance/online learning. As a result, various efforts are needed to increase students' learning motivation in every learning activity. In an effort to improve the learning process, this study aims to describe the application of educators’ roles (didactic, reflective, affective roles) and to find out the inhibiting factors faced by educators (didactic, reflective, affective roles) to enhance motivation to learn social science during the Covid-19 pandemic. The approach used in this study was a descriptive qualitative approach. The data sources in this study included primary sources and secondary sources. The primary source was interviews with social science teachers at Islamic secondary schools (MTs) in Sumbergempol District, Tulungagung. Meanwhile, secondary sources were the documents obtained at the research sites. These data were collected by conducting observation, interviews, and documentation. The results of the study indicate that: (1) The applications of educators’ roles (didactic, reflective, affective roles) to enhance motivation to learn social science during the Covid-19 pandemic are as follows: in applying the didactic role, the educators used learning resources such as textbooks and worksheets. The technique to deliver the materials was summarizing the materials in the form of Word/PDF or explaining the materials through voice notes. The instructional media used by the educators were pictures, WhatsApp, E-learning, and Google Forms. In applying the reflective role, the educators implemented the scientific learning approach. The methods used by the eudcators varied such as the lecture, question and answer, and assignment methods. The instructional models adopted by the educators were discovery learning and problem-based learning. In addition, the educators conducted evaluations at the beginning or at the end of learning to determine the level of success. In applying the affective role, the educators provided good examples and continuous advice. They also sometimes gave threats or even punishments so that students can learn their lesson. (2) The inhibiting factors faced by the educators to enhance motivation to learn social science during the Covid-19 pandemic were the internal factors including lack of learning interest and difficulty in understanding the material. Meanwhile, the external factors were financial constraints and inadequate school facilities. Abstrak Selama masa pandemi COVID-19, aktivitas belajar siswa terhadap minat belajar berangsur-angsur menurun. Hal ini dikarenakan penerapan pembelajaran jarak jauh/online. Oleh karena itu diperlukan berbagai upaya untuk meningkatkan motivasi belajar siswa dalam setiap kegiatan pembelajaran. Dalam upaya meningkatkan proses pembelajaran, penelitian ini bertujuan untuk mendeskripsikan penerapan peran pendidik (peran didaktis, reflektif, afektif) dan untuk mengetahui faktor penghambat yang dihadapi pendidik (peran didaktis, reflektif, afektif) untuk meningkatkan motivasi belajar. belajar ilmu sosial di masa pandemi Covid-19. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif deskriptif. Sumber data dalam penelitian ini meliputi sumber primer dan sumber sekunder. Sumber primer adalah wawancara dengan guru IPS MTs di Kecamatan Sumbergempol, Tulungagung. Sedangkan sumber sekunder adalah dokumen-dokumen yang diperoleh di lokasi penelitian. Pengumpulan data dilakukan dengan melakukan observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa: (1) Penerapan peran pendidik (peran didaktis, reflektif, afektif) untuk meningkatkan motivasi belajar IPS pada masa pandemi Covid-19 adalah sebagai berikut: dalam penerapan peran didaktis, pendidik menggunakan sumber belajar seperti buku teks dan lembar kerja. Teknik penyampaian materi adalah meringkas materi dalam bentuk Word/PDF atau menjelaskan materi melalui voice note. Media pembelajaran yang digunakan pendidik adalah gambar, WhatsApp, E-learning, dan Google Forms. Dalam menerapkan peran reflektif, pendidik menerapkan pendekatan pembelajaran saintifik. Metode yang digunakan oleh para penyuluh bervariasi seperti metode ceramah, tanya jawab, dan penugasan. Model pembelajaran yang diadopsi oleh pendidik adalah discovery learning dan problem-based learning. Selain itu, pendidik melakukan evaluasi di awal atau di akhir pembelajaran untuk mengetahui tingkat keberhasilannya. Dalam menerapkan peran afektif, pendidik memberikan contoh yang baik dan nasihat yang berkesinambungan. Mereka juga terkadang memberikan ancaman atau bahkan hukuman agar siswa dapat mempelajari pelajarannya. (2) Faktor penghambat yang dihadapi pendidik untuk meningkatkan motivasi belajar IPS di masa pandemi Covid-19 adalah faktor internal antara lain kurangnya minat belajar dan kesulitan dalam memahami materi. Sedangkan faktor eksternal adalah kendala keuangan dan fasilitas sekolah yang belum memadai.